Vitamin D status and VO2peak during a skate treadmill graded exercise test in competitive ice hockey players - Fitzgerald, J. S.; Peterson, B. J.; Warpeha, J. M.; Wilson, P. B.; Rhodes, G. S.; Ingraham, S. J. (The Journal of Strength and Conditioning Research, 2014)
Vitamin D status has been associated with cardiorespiratory fitness (CRF) in cross-sectional investigations in the general population. Data characterizing the association between 25-hydroxyvitamin D (25(OH)D) concentration and CRF in athletes are lacking. Junior and collegiate ice hockey players were recruited from the Minneapolis, MN (44.9° N), area during the off-season period (May 16-June 28). The purpose of this study was to examine the cross-sectional association between 25(OH)D concentration and CRF in a sample population of competitive ice hockey players. Circulating 25(OH)D level was assessed from a capillary blood sample analyzed using liquid chromatography-tandem mass spectrometry. Vo2peak during a skate treadmill graded exercise test (GXT) was used to assess CRF. Data on both 25(OH)D concentration and Vo2peak were available for 52 athletes. Insufficient 25(OH)D concentrations were found in 37.7% of the athletes (<32 ng/ml). Vitamin D status was not significantly associated with any physiological or physical parameter during the skate treadmill GXT.